IDIOPATHIC ACQUIRED NONHISTAMINERGIC ANGIOEDEMA - A case report - Snezhana Murgova; Chavdar Balabanov; Evgenia Barzashka (Peytchinski Publishing, 2019)
Angioedema is a self-limited, localized swelling that involves subcutaneous tissue or mucosa of the face and other areas. It affects males and females equally, usually during the 3rd and 4th decades of life. We present a patient with angioedema of the head and neck with a typical clinical picture of an acquired type and with a normal level of C1-INH. Initially, the patient was treated with a combination of drugs for allergy. However the swelling did not respond to the therapy and fresh frozen plasma was added. After the 10th day, the edema began reducing progressively. Despite the controversies in the literature we demonstrate that FFP is useful not only to ameliorate the acute attack but also for prophylaxis.